Reducing the Fuel Use Intensity of Fisheries: Through Efficient Fishing Techniques and Recovered Fish Stocks - Bastardie, Francois; Hornborg, Sara; Ziegler, Friederike; Gislason, Henrik; Eigaard, Ole Ritzau (Frontiers in Marine Science, 2022)
Understanding the drivers of greenhouse gas emissions in food production systems is becoming urgent. For wild capture fisheries, fuel use during the fishing phase generally dominates emissions and is highly variable between fisheries. Fuel use is also essential for the economy of the fisheries, but fuel-intensive fisheries can still be profitable due to fuel subsidies, in particular, if the target species is of high value. Developing an innovative bottom-up approach based on detailed catch and spatial fishing effort data, in the absence of direct fuel data, we analysed the fuel use intensity (fuel use per kg landed) and economic efficiency (landing value per litre fuel used) of Danish capture fisheries for the period 2005-2019. An overall decline in fishing effort did not significantly affect the overall fuel use intensity and efficiency, which was stable for most of the fleet segments and marine species. Robust differences in fuel use intensity among individual fisheries, reflected differential spatial accessibility and vulnerability of target species to fishing. In addition, different fishing techniques targeting the same set of species showed differences in fuel use per unit landed. Danish seining and gillnets had a lower fuel use intensity and higher economic efficiency than demersal trawling; and purse seining than pelagic trawling. The variability between stocks and fleets also indicates that there is generally potential for improvement in overall efficiency from improved stock status. Short-term management actions to promote the best available fuel-efficient fishing techniques combined with additional long-term actions to secure the recovery of stocks have the potential to reduce fishery greenhouse gas emissions. Sustainable fisheries and normative environmental management are crucial to developing incentives towards reducing fuel use whenever the fishing sector industry and science work jointly at implementing solutions, as incentives for the industry to reduce fuel use are limited as long as the fishing activity is profitable.